Persecuted mammals as indicators of moderate human disturbance in the Peruvian Amazon - Zwicker, Samantha; Singer, Dylan; Gardner, Beth (Frontiers in Conservation Science, 2025)
Human population growth, land conversion, and hunting are accelerating defaunation in tropical forests. We asked how anthropogenic and ecological factors shape the site use (occupancy) of medium- to large-bodied mammals in an unprotected Amazonian landscape. From 2015–2022 we deployed camera traps at 293 stations across 12 spatially independent grids in four areas along the Las Piedras River, Madre de Dios, Peru. Using single-season, single-species occupancy models for 17 species, we evaluated anthropogenic covariates (distance to settlements, proximity to agriculture, land-use class: Conservation vs Mixed-Use) and environmental covariates (macrohabitat: floodplain vs terra firme, distance to river, Enhanced Vegetation Index, small/large prey indices). Detection was modeled with trail type (human vs wildlife trails/roads) and operable trap nights. We recorded 14,849 detections. Persecuted species showed strong responses to human disturbance: lowland tapir occupancy was lower near agriculture, and jaguar avoided agricultural sites. Environmental gradients were also important: for example, collared peccary occupancy increased near rivers, and ocelot and lowland tapir were more frequent in floodplain forest. Detection varied among species and was influenced by trail type—large felids were more often detected on human trails, whereas some prey were more frequently detected on wildlife trails. Both anthropogenic pressure and habitat features structure mammal assemblages in this unprotected region. Persecuted species provide sensitive indicators of ecosystem condition in mixed-use forests. Management should prioritize protecting riverine habitats and mitigating disturbance near agriculture, while tailoring actions to species-specific responses.